2008
DOI: 10.1093/jac/dkn029
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CYP2B6 983T>C polymorphism on non-nucleoside reverse transcriptase inhibitor plasma concentrations in HIV-infected patients

Abstract: This is the first report that the 983T>C genotype (part of the CYP2B6*18 haplotype) impacts on nevirapine plasma concentrations and the first study to assess the impact of 983C homozygosity on efavirenz concentrations. These data have implications for administration of non-nucleoside reverse transcriptase inhibitors to Black patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
165
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(177 citation statements)
references
References 16 publications
10
165
2
Order By: Relevance
“…Plasma concentration average of our population was 6,360 µg/L ± 539 µg/L. It is definitely higher than those found by Poeta and Wyen, which were respectively 2,200 and 2,077µg/L [15][16]. In the studies preceding ours, plasma concentrations averages were included in the therapeutic index described [1,000-4,000 µg/L].…”
Section: Efavirenz Plasma Concentrationscontrasting
confidence: 51%
“…Plasma concentration average of our population was 6,360 µg/L ± 539 µg/L. It is definitely higher than those found by Poeta and Wyen, which were respectively 2,200 and 2,077µg/L [15][16]. In the studies preceding ours, plasma concentrations averages were included in the therapeutic index described [1,000-4,000 µg/L].…”
Section: Efavirenz Plasma Concentrationscontrasting
confidence: 51%
“…The functional significance of most of these variants is not yet known (131). However, recent studies have shown that two polymorphisms (983T>C and 516G>T), found at a higher frequency in African populations relative to non-Africans, are associated with a reduction in CYP2B6 protein expression as well as a large increase in levels of the antiretroviral drug efavirenz in the plasma of African HIV patients (130,145,239).…”
Section: Pharmacogeneticsmentioning
confidence: 99%
“…Subjects homozygous for the CYP2B6*6 allele, that contains both 516G>T and the 785A>G polymorphisms, display significantly higher EFV plasma levels than heterozygous subjects or those with the common genotype [10]. The 983T>C polymorphism, a less frequent polymorphism only described in Hispanic and black populations, has been shown to impact in EFV exposure as well [11,12]. In a recent study, Ribaudo et al [13] established that the CYP2B6*18 allele, that harbours the 516G>T and 983T>C polymorphisms, better predict EFV pharmacokinetics and also, slow-metabolizer genotypes were associated with increased CNS events among white patients and decreased virologic failure among black patients.…”
Section: Pharmacogenetics Of Nevirapinementioning
confidence: 99%
“…Several studies have reported that the polymorphisms 516G>T and 983T>C in the CYP2B6 gene are associated with variations in NVP pharmacokinetics in ethnically diverse populations [32][33][34][35][36], although the clinical impact remains uncertain since an association between greater NVP exposure and toxic effects has not been fully demonstrated.…”
Section: Cyp2b6-g516gg (Common Genotype)mentioning
confidence: 99%